The Influence of Organizational Culture, Personality, and Trust toward Organizational Commitment of Outlet Leader in Bank Negara Indonesia, Regional Office, Senayan Jakarta. (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this research is to determine the influence of organizational culture, personality, and trust toward organizational commitment of outlet leader in Bank Negara Indonesia, Regional Office, Senayan Jakarta. The study was conducted on organizational commitment of 98 outlet leaders selected from the target population of outlet leaders using a quantitative approach with path analysis method. Hypothesis testing shows: (1) organizational culture has a direct positive effect on organizational commitment; (2) personality has a direct positive effect on organizational commitment; (3 trust has a direct positive effect on organizational commitment; (4) organizational culture has a direct positive effect on trust: (5) personality has a direct positive effect on trust (6) organizational culture has a direct positive effect on the personality: To improve the commitment of the organization of outlet leaders in Bank Negara Indonesia, the Regional Office of Senayan Jakarta. It needs to be enhanced organizational culture, personality and trust